Renal Function Assessment As An Independent Predictor Of Prognosis In Patients With Acute Coronary Syndrome - Saidov M.A; Khasanzhanova F.O; Nizamov Kh.Sh; Kushnazarov R.S; Ochilova M.Kh (Genius Journals, 2023)
This study was conducted on the basis of the Samarkand regional branch of the Republican Specialized Scientific and Practical Medical Center of Cardiology (SRF RSNPMC). The study investigated the prognostic value of renal dysfunction as a risk factor for cardiovascular death in patients with acute coronary syndrome (ACS). The study included 122 patients with ACS aged 32 to 85 years. All patients underwent a general clinical examination (collection anamnesis, anthropometric and physical examination of the patient, measurement of blood pressure, heart rate). Laboratory and instrumental examination included clinical blood tests, biochemical blood test on admission and in dynamics on the 2nd and 7th days of admission, ECG, echocardiography. A decrease in GFR of less than 60 mL/min affects cardiovascular mortality in patients with STEMI, but does not affect the prognosis in patients with STIM. The widespread introduction of the GFR calculation method will make it possible to timely detect even a moderate impairment of the filtration function of the kidneys and make corrections to the patient's therapy, thereby reducing the number of adverse outcomes.
Keywords: Acute coronary syndrome; kidneys; kidneysechocardiography